2002
DOI: 10.1088/0264-9381/19/16/313
|View full text |Cite
|
Sign up to set email alerts
|

CYK tensors, Maxwell field and conserved quantities for the spin-2 field

Abstract: Starting from an important application of Conformal Yano-Killing tensors for the existence of global charges in gravity (which has been performed in [17] and [18]), some new observations at I + are given. They allow to define asymptotic charges (at future null infinity) in terms of the Weyl tensor together with their fluxes through I + . It occurs that some of them play a role of obstructions for the existence of angular momentum. Moreover, new relations between solutions of the Maxwell equations and the spin-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…By direct calculations we observed that (18) and (19) admit three Killing vectors given by (13) and a (KY) tensor having the following non-zero components…”
Section: The Singular Casementioning
confidence: 99%
See 1 more Smart Citation
“…By direct calculations we observed that (18) and (19) admit three Killing vectors given by (13) and a (KY) tensor having the following non-zero components…”
Section: The Singular Casementioning
confidence: 99%
“…In the last yers a huge effort was devoted for analyzing the importance of (KY) tensors [9,10,11,12,13,14,15] in several areas but there are relatively few manifolds of physical interest admitting these tensors. This drawback is mainly because (KY) tensors are antisymmetric and their equations impose restrictions on the manifold structure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Conserved quantities which are linear with respect to CYK tensor were investigated many times (cf. [6], [7], [9], [10], [12], [15], [16]). On the other hand, quadratic charges are less known and have usually been examined in terms of the Bel-Robinson tensor (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to [28] one can define, in terms of spacetime curvature, two kinds of conserved quantities with the help of conformal Yano-Killing tensors (or shortly CYK tensors, sometimes called conformal Killing forms or twistor forms, see e.g. [30,38,39]).…”
Section: Introductionmentioning
confidence: 99%
“…The first kind is linear and the second quadratic with respect to the Weyl tensor, but a basis for both of them is the Maxwell field. Conserved quantities which are linear with respect to the CYK tensor were investigated many times (cf [1,21,22,25,26,28,35,36]). On the other hand, quadratic charges are less known and have usually been examined in terms of the Bel-Robinson tensor (see e.g.…”
Section: Introductionmentioning
confidence: 99%